2006
DOI: 10.1051/0004-6361:20065065
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and evolution of an eruptive flare

Abstract: Aims. We study the dynamics and the evolution of a C2.3 two-ribbon flare, developed on 2002 August 11, during the impulsive phase as well as during the long gradual phase. To this end we obtained multiwavelength observations using the CDS spectrometer aboard SOHO, facilities at the National Solar Observatory/Sacramento Peak, and the TRACE and RHESSI spacecrafts. . In one footpoint simultaneous Hα data are also available and we find, at the same time and location, downflows with an inferred velocity between 4 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 51 publications
8
45
0
Order By: Relevance
“…The observed flow velocities in comparison with predictions of hydrodynamic simulations were studied by Brosius & Phillips (2004), who report observations of a flare jointly observed by CDS and Yohkoh/BCS suggesting momentum balance between up-and downward flowing material in the impulsive phase. Teriaca et al (2006) find an order of magnitude agreement of the momenta of cospatial, oppositely directed flows in a small two ribbon flare. The combination of flare X-ray spectra and images and CDS Doppler velocities enabled Milligan et al (2006) to demonstrate observations in rough agreement with simulations of explosive chromospheric evaporation.…”
Section: Introductionmentioning
confidence: 57%
“…The observed flow velocities in comparison with predictions of hydrodynamic simulations were studied by Brosius & Phillips (2004), who report observations of a flare jointly observed by CDS and Yohkoh/BCS suggesting momentum balance between up-and downward flowing material in the impulsive phase. Teriaca et al (2006) find an order of magnitude agreement of the momenta of cospatial, oppositely directed flows in a small two ribbon flare. The combination of flare X-ray spectra and images and CDS Doppler velocities enabled Milligan et al (2006) to demonstrate observations in rough agreement with simulations of explosive chromospheric evaporation.…”
Section: Introductionmentioning
confidence: 57%
“…Other observations without HXRs have instead used the time derivative of the GOES flux (assuming the Neupert effect) to identify the impulsive phase (Teriaca et al 2006;Del Zanna et al 2006). Spectroscopy from CDS at high time cadence (10 s) of a "flare-like transient" has also been obtained (Brosius & Holman 2007).…”
Section: Chromospheric Evaporationmentioning
confidence: 99%
“…Simulations predict that downflows are noticeable only in spectral lines formed below transition region temperatures and that they reach velocities of several tens of km s −1 because of the higher mass and inertia of the chromospheric material (Fisher et al 1985;Allred et al 2005;Reep et al 2015). Observational evidence for the proposed momentum balance during explosive evaporation was found for several events (Zarro et al 1988;Teriaca et al 2006;Milligan et al 2006a). Other observational studies, however, also revealed downflows at coronal temperatures (Milligan & Dennis 2009;Young et al 2013), suggesting that the flaring atmosphere is very dynamic and complex on small spatial scales (e.g., Veronig et al 2010).…”
Section: Introductionmentioning
confidence: 96%